Penile fracture rare urological emergency - Shakya, Prateek; Choudhary, Bhuvan; Tripathi, Komal; Sawai, Malvika (International Surgery Journal, 2016)
Penile fracture is a rare complication which occurs at the time of sexual intercourse. It is an emergency condition and usually diagnosis is made by clinical examination. Immediate surgical repair is done to avoid physiological and psychological consequences. Here we present one case of penile fracture which occurred during sexual intercourse and was immediately repaired with no postoperative complications.